‘Rites of Passage’ and the Writing of Church History: Reflections upon our Craft in the Aftermath of van Gennep - O'Loughlin, Thomas (Studies in church history, 2023)
Van Gennep's work on rites of passage can be viewed as part of the rise of anthropology in the period prior to the First World War, and has been very influential conceptually and on the practice of churches ever since. This article examines how his own historical work, taking baptism as an example of a rite of passage, compares with the practice of church history at the time. It then seeks to assess van Gennep's assumptions in comparison with the assumptions about the past used in church history writing today, acknowledging that the turn to plurality - that uniformity in doctrines, rituals and texts is subsequent to diversity - of recent scholarship is in several respects anticipated by van Gennep.